Progress in Top-Down LC-MS Analysis of Antibodies: Review - You, Jiwon; Park, Hae-Min (Biotechnology and bioprocess engineering, 2023)
Antibodies are large heterogenous proteins due to post-translational modifications, including glycosylation. Structural analysis of antibodies by mass spectrometry has been of great interest recently, especially in the pharmaceutical industry. Over the past decade, bottom-up mass spectrometry has been widely used to identify single protein targets and whole proteomes from a biological system such as a cell, tissue, or organism. However, due to the protein inference problem in bottom-up mass spectrometry, this approach has intrinsic limitations for characterizing the post-translationally modified forms of proteins such as antibodies. In contrast to bottom-up mass spectrometry measuring peptides produced from proteins by proteolytic digestion, top-down mass spectrometry is a powerful technology that allows measuring proteins without proteolysis, thus characterizing intact forms of proteins, which provides information on primary sequences, including modifications characterization. In this review, we outline some progress in the separation, ionization, and fragmentation of intact proteins for top-down mass spectrometry and the growing power of intact protein-resolved measurements in biotechnology.